Fish Biodiversity in Poigar River Estuary North Sulawesi - Rizaldy A. Rangian; Ruddy D. Moningkey; Nego E. Bataragoa (Sam Ratulangi University, 2019)
The purpose of this study was to determine the diversity and size variation of fish caught in the Poigar River Estuary. Sampling was carried out on tide and low tide in the New Moon and Full Moon phases using beach trawl. The catch gets 42 species, 2,726 individuals and weighs 11,355.5 g. The dominance index at low tide and water recedes 0.47 and 0.44 respectively. Diversity Index at high tide and low tide are 0.93 and 1.11 respectively. Found 10 important fish species in tide and 13 species at low tide, there are four species which are important fish both at low tide and high tide, namely Ambassis urotaenia, Ambassis intetrupta, Gazza minuta and Gerres filamentosus. The size distribution of fish from the juvenile phase to the adult phase is the Ambassis urotaenia with a distribution size of 4.2 cm to 9.0 cm and the Ambassis interupta 4.3 to 9.7 cm. Fish classified as only in the juvenile phase are Gazza minuta with a distribution size of 4.0 cm to 12.9 cm and Gerres filamentosus 6.3 cm to 8.6 cm.Kata kunci: Biodiversity, River Poigar, species, juvenile and adult.ABSTRAKTujuan penelitian ini adalah untuk mengetahui keanekaragaman dan variasi ukuran ikan yang tertangkap di Muara Sungai Poigar. Pengambilan sampel dilakukan pada air pasang dan air surut pada fase Bulan Baru dan Bulan Purnama dengan menggunakan pukat pantai. Hasil tangkapan mendapatkan 42 spesies, 2.726 individu dan berat 11.355,5 g. Indeks dominasi pada saat air pasang dan air surut masing-masing 0,47 dan 0,44. Indeks Keanekaragaman pada saat air pasang dan surut pasang-masing sebesar 0,93 dan 1,11. Ditemukan 10 spesies ikan penting pada air pasang dan 13 spesies pada air surut, terdapat empat spesies yang merupakan ikan penting baik pada saat surut maupun pasang yaitu Ambassis urotaenia, Ambassis intetrupta, Gazza minuta dan Gerres filamentosus. Sebaran ukuran ikan dari fase juvenile sampai fase dewasa adalah Ambassis urotania dengan sebaran ukuran 4,2 cm sampai 9,0 cm dan Ambassis intetrupta 4,3 cm sampai 9,7 cm. Ikan yang tergolong hanya pada fase juvenile adalah Gazza minuta dengan sebaran ukuran 4,0 cm sampai 12,9 cm dan Gerres filamentosus 6,3 cm sampai 8,6 cm.Kata kunci: Biodiversitas, Sungai Poigar, spesies, juvenile dan dewasa.